EMPIRICAL ANALYSIS OF THE CORPORATE GOVERNANCE SYSTEM IN UZBEKISTAN - Elmurod Abdusattorovich Khoshimov; Akmal Ayibjan ogli Tursunbaev (Western European Studies, 2025)
This study presents an empirical analysis of the corporate governance system in Uzbekistan during the years 2020–2023. As Uzbekistan continues its transition toward a market-based economy, the importance of transparent and accountable corporate governance practices has grown significantly. This paper analyzes the structure, trends, and challenges of Uzbekistan’s corporate governance reforms by using key performance indicators such as shareholder participation, transparency, privatization rates, and compliance with international financial reporting standards (IFRS). The findings reveal a positive but gradual shift toward international governance standards. However, institutional and regulatory barriers remain. The study concludes with practical recommendations aimed at accelerating governance reforms and improving investor confidence.
Keywords: Corporate governance; Uzbekistan